CARBOHYDRATE METABOLISM DISORDERS AND CORONARY HEART DISEASE: PROGNOSTIC VALUE AND REVASCULARISATION EFFECTIVENESS - L. V. Kremneva; T. S. Pursanova; O. V. Abaturova (Кардиоваскулярная терапия и профилактика, 2013)
This literature review presents the data on the prevalence and prognostic value of carbohydrate metabolism disorders, such as Type 2 diabetes mellitus (DM) and pre-diabetes — fasting hyperglycaemia and impaired glucose tolerance), among patients with coronary heart disease (CHD). The authors present the results of large studies on comparative effectiveness of modern pharmacological treatment and myocardial revascularisation (percutaneous coronary intervention and coronary artery bypass graft surgery) in patients with CHD and DM.